Evidence-Based Decision Making for Nutrition Policy and Programme Formulation in Ethiopia: A Qualitative Study Exploring Barriers and Facilitators - Hailu, Solomon Eshetu (Curr Dev Nutr, 2020)
OBJECTIVES: Despite much nutrition research conducted in Ethiopia, none has described existing opportunities for synergy or possible missed opportunities to use research to inform policy and program decisions to foster accelerated progress. The study aimed to describe prevailing processes on evidence use in formulating nutrition policy and program decisions and identify potential barriers and opportunities for evidence-based decision-making for nutrition for Ethiopia's context. METHODS: In 2017, 29 purposively selected key informants (KIs) were interviewed. They were identified using a consultative stakeholder mapping workshop and represented National Nutrition Program coordinators, key actors in government sectors, program coordinators from selected local and international NGOs, local and international universities and research institutes involved in nutrition research and key actors in policy decision-making. A framework analysis including identifying themes, coding, indexing, charting, mapping and interpretation was used. A validation workshop discussed findings and added perspectives to interpretation. RESULTS: The KIs perceived that demand for evidence from the Ethiopian government had been increasing over time. Majority referred to poor research quality as a barrier for using research in decision-making processes. Other challenges identified included limited cross-linkage, coordination gaps between researchers and decision makers, and inadequate translation of research evidence into meaningful information for policy makers. Availability of different forums, research dissemination conferences and suitable institutional structures that enable research and evidence dissemination were considered to be opportunities that should be leveraged to inform policy making. CONCLUSIONS: The quality of research, and of collaborative engagement between those who produce evidence and decision makers who formulate policies need to be strengthened. Regular evidence dissemination events and publication of action oriented easy to read briefs could increase use of evidence among nutrition policy makers. FUNDING SOURCES: Ethiopian Public Health Institute and Evidence-informed Decision-making in Health and Nutrition Network.